Does Social Capital Affect SME's Performance? - Sri Palupi Prabandari; Ida Yulianti (International Journal of Social Service and Research, 2023)
The performance of SMEs is a major concern for strengthening businesses to survive in dynamic market conditions. Often, these enterprises cannot fund risky assets due to limited support sources. Tangible and intangible resources can undoubtedly enhance the profitability of SME businesses. Encouraging SMEs to recognize alternative opportunities is crucial for their survival in the market. This study contributes theoretically by examining the role of intangible (non-financial) resources, such as social capital, given the unique typology of SMEs. Despite receiving relatively little attention, this aspect can provide a competitive advantage. The study utilized qualitative methods, with a systematic literature review (SLR) chosen to address the research questions. The study results indicate that social capital plays a significant role in business success. Businesses with strong social capital, including networks, norms, and trust, exhibit resilience and can be passed down from generation to generation, supporting the performance of SMEs. Evaluating the performance of SMEs solely in terms of financial capital is not appropriate, as these businesses typically operate on a minimal scale, limiting the availability of financial reports.